Regulating use of the internet in public libraries: a review. Issue 3 (6th May 2014) - Spacey, Rachel; Cooke, Louise; Muir, Adrienne; Creaser, Claire
Abstract : Purpose: – The purpose of this paper is to review current knowledge, research and thinking about the difficulties facing public libraries offering internet access to their users in ensuring legally compliant and non-offensive use of this facility whilst still adhering to the professional value of freedom of access to information. Design/methodology/approach: – A range of recently published sources (1997-2013) relating to the technical and organisational measures used to manage public internet access primarily in public libraries in the UK with some limited international examples were reviewed and analysed. This work was undertaken as the underpinning research for an AHRC-funded project, MAIPLE (Managing Access to the internet in Public Libraries). Findings: – The provision of public internet access is a well-established component of the role of public libraries, but is seen as a potential problem due to the possibility of misuse, and it appears that simplistic technical solutions have disappointed. Legislation increases the need for more effective solutions that can provide a balance between the need for legal compliance, a welcoming environment for users, and the protection of key freedoms. A range of measures are being adopted worldwide in response to this dilemma. Originality/value: – Research exploring internet access in public libraries and its management in the UK is numerically small and much of it dates back to the start of the twenty-first century. This review presents a comprehensive analysis of the available literature and is of relevance to practitioners and academics in the fields of public librarianship.